Predicting the future of urodynamics - Smith, Ariana L.; Wein, Alan J. (Translational Andrology and Urology, 2012)
The clinical assessment of lower urinary tract dysfunction has been supported by objective measures obtained during urodynamics (UDS) for more than 30 years. Over this time, equipment has evolved with several technological advances, understanding has progressed with achievement of many milestones in UDS research, and access to care has improved with UDS equipment present in many health care centers throughout the developed world.